PRESERVING TRADITIONAL RITUALS AS LOCAL CULTURAL HERITAGE IN JAYAPURA, PAPUA: A STUDY ON THE ROLE OF INDIGENOUS COMMUNITIES IN SUSTAINING ANCESTRAL TRADITIONS - Linda Safitri (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
The preservation of traditional rituals is a vital aspect of safeguarding local cultural heritage amidst the growing influence of globalization that threatens regional cultural identities. This study aims to examine the role of indigenous communities in sustaining traditional rituals in the Jayapura region of Papua. Using a qualitative research method with an ethnographic approach, the study involved participant observation and in-depth interviews with traditional leaders, community figures, and youth representatives. The findings reveal that indigenous communities actively preserve rituals through the inter generational transmission of cultural values, youth involvement in customary activities, and the integration of ritual practices into social and religious events. Despite external pressures such as modernization and lifestyle changes, indigenous communities remain strongly committed to sustaining their ancestral traditions. This research highlights the importance of involving local communities in the formulation of cultural preservation policies to ensure the continuity of cultural heritage in Papua.